Predictive value on diffusion weighted imaging scores for basilar artery occlusion after endovascular treatment. Issue 1 (February 2021) - Wan, Can; Wu, Guangliang; Jin, Xing; Liao, Shaojun; Zhang, Foming; Hu, Mingzhe; Meng, Miaomiao; Guo, Yixin; You, Jinsong
Purpose: To assess the predictive value of three scoring systems based on diffusion weighted imaging in basilar artery occlusion patients after endovascular treatment. Methods: We analyzed clinical and radiological data of patients with basilar artery occlusion from January 2010 to June 2019, with modified Rankin Scale of 0–2 and 3–6 defined as favorable outcome and unfavorable outcome at three months. Diffusion weighted imaging posterior circulation ASPECTS Score (DWI pc-ASPECT Score), Renard diffusion weighted imaging Score, and diffusion weighted imaging Brainstem Score were used to evaluate the early ischemic changes. Results: There were a total of 88 basilar artery occlusion patients enrolled in the study after endovascular treatment, with 33 of them getting a favorable outcome. According to the analysis, the time from onset to puncture within 12 h (odds ratio: 4.34; 95% confidence interval: 1.55–12.16; P = 0.01), presence of collateral flow via PCoA (odds ratio: 0.31; 95%CI: 0.12–0.79; P = 0.01) or between PICA and SCA (odds ratio: 0.18; 95%CI: 0.07–0.47; P = 0.00), equal or less than 15 points on baseline NIHSS (area under the curve 0.79, 95% CI 0.69–0.89; sensitivity = 69.1%, specificity = 81.8%; P = 0.00), and equal or less than 1.5 points on diffusion weighted imaging Renard score (area under the curve 0.63, 95% CI 0.51–0.75; sensitivity = 83.6%, specificity = 39.4%; P = 0.046) were independently associated with favorable outcome. Conclusions: Renard diffusion weighted imaging score may be an independent predictor of functional outcome in basilar artery occlusion patients after endovascular treatment.